Spintronics: Electrical Control of Perpendicular Magnetic Anisotropy and Spin‐Orbit Torque‐Induced Magnetization Switching (Adv. Electron. Mater. 3/2020). (9th March 2020) - Huang, Qikun; Dong, Yanan; Zhao, Xiaonan; Wang, Jing; Chen, Yanxue; Bai, Lihui; Dai, Ying; Dai, Youyong; Yan, Shishen; Tian, Yufeng
Abstract : In article number 1900782, Yufeng Tian and co‐workers demonstrate that exchange coupling of magnetic moments across the Co/CoO interface provides an extra source of stabilization for the perpendicular magnetic anisotropy (PMA) in heterojunctions with a core structure of Pt/Co/CoO/TiO2 (TaOx). The inside cover image shows a representation of this system, with the background showing a Pt/Co/CoO/oxide/Pt cell crossbar array on a chip and the center showing an enlarged view.